2023
DOI: 10.1097/ee9.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Associations between weekly gestational exposure of fine particulate matter, ozone, and nitrogen dioxide and preterm birth in a North Carolina Birth Cohort, 2003–2015

Alison K. Krajewski,
Thomas J. Luben,
Joshua L. Warren
et al.

Abstract: Background: Preterm birth (PTB; <37 weeks completed gestation) is associated with exposure to air pollution, though variability in association magnitude and direction across exposure windows exists. We evaluated associations between weekly gestational exposure to fine particulate matter (PM2.5), nitrogen dioxide (NO2), and ozone (O3) with PTB in a North Carolina Birth Cohort from 2003 to 2015 (N = 1,367,517). Methods: Daily average PM2.5 and daily 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We evaluated air pollution exposures over trimesters of pregnancy. Previous studies have examined weeks and months of pregnancy as well ( 69 , 70 ), though inconsistency in the exposure window associated with preterm birth is a noted uncertainty ( 32 – 34 ). For example, Krajewski et al ( 70 ) reported an increased risk of PTB associated with PM 2.5 and O 3 exposure across gestational weeks and generally null effects for NO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated air pollution exposures over trimesters of pregnancy. Previous studies have examined weeks and months of pregnancy as well ( 69 , 70 ), though inconsistency in the exposure window associated with preterm birth is a noted uncertainty ( 32 – 34 ). For example, Krajewski et al ( 70 ) reported an increased risk of PTB associated with PM 2.5 and O 3 exposure across gestational weeks and generally null effects for NO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined weeks and months of pregnancy as well ( 69 , 70 ), though inconsistency in the exposure window associated with preterm birth is a noted uncertainty ( 32 – 34 ). For example, Krajewski et al ( 70 ) reported an increased risk of PTB associated with PM 2.5 and O 3 exposure across gestational weeks and generally null effects for NO 2 . Alman et al ( 69 ) observed elevated odds of preterm birth with PM2.5 exposure in months 3 and 4 as well as weeks 9–12, while Wang et al reported increased hazard ratios for weeks 20–28 for PM 2.5 , 18–31 for NO 2 , and 23–31 for O 3 ( 71 ).…”
Section: Discussionmentioning
confidence: 99%